Réponses

2013-12-01T11:11:09+01:00
Salut,voici les réponses:
a) 5-2x(-3+(-10)) = 5-2x(-13) =5-(-26)= 5+26= 31
b) 0.1-2+(2.5-21)x2= 0.1-2+(-18.5)x2= 0.1-2+(-37)= -39+0.1= -38.9
c) -2-21+15 / -3-8+6= -23+15 /-11+6= -8/-5= 8/5
d) -2+3(-2-(-3+2x(-27)-2x(-3))= -2+3(-2-(-3+(-54)+(+6))= 2+3(-2-(-57+6))=2+3(-2-(-51))=
                                                                                                       2+3(-2+51)
                                                                                                       2+3(49)
                                                                                                       2+147=149

j'espère ne pas m'etre trompée dans les calculs